2021
DOI: 10.1128/aac.01539-20
|View full text |Cite
|
Sign up to set email alerts
|

Parasite-Host Dynamics throughout Antimalarial Drug Development Stages Complicate the Translation of Parasite Clearance

Abstract: Ensuring continued success against malaria depends on a pipeline of new antimalarials. Antimalarial drug development utilizes pre-clinical murine and experimental human malaria infection studies to evaluate drug efficacy. A sequential approach is typically adapted, with results from each stage, informing the design of the next stage of development. The validity of this approach depends on confidence that results from murine malarial studies predict the outcome of clinical trials in humans. Parasite clearance r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…We also found that these estimates do not influence the clearance half-life of nonviable parasites, which is equal to 3.76 h (95% CI, 3.26, 4.34) and 7.08 h (95% CI, 6.19, 8.11) in humans and mice, respectively. The latter observation is consistent with observations of slower parasite clearance after drug treatment in the NSG mouse model compared with human infection ( 27 ). Together, these findings suggest that although parasite viability provides a number of consistent observations between the dynamics of artesunate activity in mice and humans, differences in these infection models remain, which could not be completely reconciled by assessing parasite viability.…”
Section: Resultssupporting
confidence: 91%
“…We also found that these estimates do not influence the clearance half-life of nonviable parasites, which is equal to 3.76 h (95% CI, 3.26, 4.34) and 7.08 h (95% CI, 6.19, 8.11) in humans and mice, respectively. The latter observation is consistent with observations of slower parasite clearance after drug treatment in the NSG mouse model compared with human infection ( 27 ). Together, these findings suggest that although parasite viability provides a number of consistent observations between the dynamics of artesunate activity in mice and humans, differences in these infection models remain, which could not be completely reconciled by assessing parasite viability.…”
Section: Resultssupporting
confidence: 91%
“…We fit the model to the data using a Bayesian hierarchical modeling method, which is a well-established method for estimating biological parameters and has been used in many quantitative studies. 36 39 Briefly, Bayesian inference is a statistical method to update our existing knowledge about the distribution of the biological parameter of interest (referred to as the prior distribution) by integrating the information from a set of novel data (by a likelihood function). The updated distribution of the parameter is called the posterior distribution, which is what we would like to obtain to provide an estimate for the parameter of interest θ.…”
Section: Methodsmentioning
confidence: 99%
“…Second, because the mechanism of action of the drug in the body is more complex than that in vitro , the in vitro single drug sensitivity test cannot reflect the synergy or addition of the drugs in the combined chemotherapy. Third, interactions of parasite-host and antimalarial drug-host are vital to the efficacy of the drugs during the in vivo study ( 40 43 ).…”
Section: Discussionmentioning
confidence: 99%